Topical Honey Application In Treating Large Ulcerated Wound As a Complication of Vascular Malformation In a 5-Month-Old Baby - Djoenaedi, Intania; Sudjatmiko, Gentur (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: The ancient Egyptians and Greeks have used honey for wound care, and a broad spectrum of wounds are treated all over the world with natural unprocessed honeys from different sources. In lots of studies, honey as a conventional wound treatment may help improve wound healing, prevent invasive infections and eliminate colonization. With the increasing frequency of antibiotic-resistant bacteria, modern medicine give attention to natural products. The aim of this report is to gain insight into the practical use of topical honey in wound management. Methods: We report a case of five-month-old girl with sepsis and large ulcerated necrotizing wound at the external genitalia and perineum extending to gluteal area as complication of vein malformation after treated with intravenous injection of Bleomycin and Vincristine. Result: She was successfully treated with unprocessed local honey. Conclusion: Honey is shown to be a good option for treating infected chronic wound with dramatic result.